Mengukur Budaya Toleran dan Nasionalisme di Lingkungan Civitas Akademika UPN “Veteran” Jogjakarta - Ir. Lestanta Budiman, M.Hum (Jurnal Paradigma, 2012)
The aims of the research are to measure tolerance culture and nationalism awareness among UPN “Veteran” population and to do philosophical reflection toward the results related with UPN “Veteran” Jogjakarta’s ideology, doctrine and its prime goal in education.The research is philosophical investigation based on sociological data and lust but not least enrich by literature or library study. Sociological data use to know the factual condition of UPN population’s tolerance culture and nasionalisme awareness, than literature data as philosophical reflection material. To collect the sociological data the research take a cluster random sampel as a metode and to reflect use the philosophical teknik methos such as interpretation, holistic and sintetic-analytic.The results of descriptive analysis show that ……………………………………………Historical and philosophical reflection show that Indonesian nation movement on the past and UPN’s doctrine and goal have similarities and spirit. Indonesia-nation build by the young generation that take lecture at STOVIA. And UPN in its Statue doctrine that his existence is to produce the true leader nationalist. Indonesia concept and “Indonesian” label is something a new that found by STOVIA students. And today, UPN’s students should have same duty to strengthening its. UPN’s mission as explored in it’s statute is to keep Indonesia-nation tree by educated and produced the huan resource that concern to nation’s and society’s complex problem